OTITIS EXTERNA IN 23 YEARS OLD WOMEN - Fatrianda Putri Cyninthia Kennedy (Fakultas Kedokteran Universitas Lampung, 2015)
Otitis externa is an inflammation of acute and chronic ear canal caused by bacteria, it can be localized or diffuse. Factors that cause otitis externa is moisture, clogging the middle ear canal, local trauma, and allergies. Otitis externa can spread to pina, periaurikular or to the temporal bone. This is a disease of the external ear that is often found. Woman, 23 years old, complaint of earache for 2 days, followed with hearing loss, but no discharge from the left ear. Based on history, physical examination, andhome visits, obtained internal factors that affect this case, among others, scraping ear habit with a cotton bud every day and less maintain hygiene. From a physical examination on the left ear obtained pain auricle movement (+), tenderness tragus (+), acoustic meatus appear edema and hyperemia. The diagnosis in this case is otitis externa. Problem solving in this case is the intervention on patients, not only in medical therapy but also in all aspects of self hygiene. [J Agromed Unila 2015; 2(1):43-46]Keywords: behavior, hygiene, otitis externa.